ANALISIS EFEKTIVITAS PENERIMAAN PAJAK RESTORAN PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA BANJARBARU TAHUN 2016 – 2019 - Lidya Nor Afifah; Ika Chandriyanti (Universitas Lambung Mangkurat, 2021)
This final project research aims to analyze the effectiveness of restaurant tax revenues at the Banjarbaru City Regional Tax and Retribution Management Agency (BPPRD) 2016 - 2019. Income from restaurant taxes is one of the regional tax sectors that contributes the largest Regional Original Income (PAD) in the City. Banjarbaru, from the results of research and data that has been obtained, it can be seen that in 2016 – 2019 the effectiveness of the restaurant tax is categorized as very effective every year due to its effectiveness level that exceeds 100%. The Banjarbaru City Regional Tax and Levy Management Agency (BPPRD) continues to maintain and increase restaurant tax revenues every year so that it can still be categorized as very effective.